PULMONARY HYPERTENSION: DIFFICULT CASE IN CLINICAL PRACTICE - D. V. Madeeva; O. M. Drapkina; M. R. Skhirtladze; I. E. Sergeev; V. T. Ivashkin (Klinicist)
Clinical case of a patient with idiopathic pulmonary hypertension, an algorithm for the diagnosis and management of patients with this pathologyare presented in the paper.